Basal Cell Adenoma-Clinicopathological, Immunohistochemical Analysis and Surgical Considerations of a Rare Salivary Gland Tumor with Review of Literature - Bhagat Singh, AD (Niger J Surg, 2015)
INTRODUCTION: Basal cell adenoma (BCA) of the salivary glands is a rare benign salivary gland tumour. Differentiation of BCA from varied entities involving maxillofacial area is mandatory. AIM: To analyze the clinicopathological, histopathologic features, immunohistochemcal analysis and surgical considerations of this rare entity. MATERIALS AND METHODS: This study included 12 cases of BCA from archives of department reported over the period of 13 years. All the pertaining clinicopathologic features such as incidence, age, sex and site of lesions were assessed. Tissue sections were stained by using panel of immunohistochemical markers, i.e. Pan CK, CK 5/6 and S100, Calponin, p63, CD 117 and smooth muscle actin. RESULTS: BCA was observed in 26-52 years age group (mean age, 38.75 years) with female propensity of 7:5 male to female ratio. It is seen more commonly in parotid gland, followed by upper lip, buccal mucosa and palate. Solid type is the most common histopathologic type followed by tubular, membranous and trabecular. Only one case of membranous type of BCA showed recurrence. Pan CK, CK 5/6 showed strong immunoreactivity, calponin showed moderate staining, p63 and Ki-67 mild staining, whereas CD 117 and SMA showed negative immunostaining. CONCLUSION: Vigilant comprehensive analysis of all the pertaining clinicopathologic and histopathologic features and immunohistochemical analysis are required for differentiating from other lesions with basaloid differentiation having varying prognosis.